ALGUNS ASPECTOS REFERENTES Ã€ BIOLOGIA E HÃBITOS DE ð˜šð˜ªð˜£ð˜ªð˜¯ð˜¦ ð˜£ð˜¢ð˜³ð˜£ð˜¢ð˜³ð˜¢ (Dyar, 1906)(LEPIDOPTERA-EUCLEIDAE) EM CAFEEIROS - Perez, C. A.; Nakano, O.; Haramoto, K. A. (REVISTA DE AGRICULTURA, 2020)
ALGUNS ASPECTOS REFERENTES Ã€ BIOLOGIA E HÃBITOS DE ð˜šð˜ªð˜£ð˜ªð˜¯ð˜¦ ð˜£ð˜¢ð˜³ð˜£ð˜¢ð˜³ð˜¢ (Dyar, 1906)(LEPIDOPTERA-EUCLEIDAE) EM CAFEEIROS